DNA microarray chip assay in new use: early diagnostic value in cutaneous mycobacterial infection - Qian Yu; Yuanyuan Wang; Zhiqin Gao; Hong Yang; Siyu Liu; Jingwen Tan; Lianjuan Yang (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionThe clinical practicability of DNA microarray chip in detecting the presence of mycobacterial species/isolates directly in the skin tissues has not been evaluated, nor the efficacy of DNA microarray chip as a novel diagnostic tool for the early diagnosis of cutaneous mycobacterial infections is known.MethodsThe present study analyzed the incidence of cutaneous mycobacterial infections in Shanghai and explored the efficacy of a novel DNA microarray chip assay for the clinical diagnosis of the disease from skin tissue specimens compared to traditional detection methods. A total of 60 participants fulfilling the defined diagnostic criteria and confirmed positive for cutaneous mycobacterial infections from 2019 to 2021 were enrolled in the study. Subsequent to recording the participants’ medical history and clinical characteristics, the skin tissue specimens were collected for analyses. The specimens underwent histopathological analyses, skin tissue culture, and DNA microarray chip assay.ResultsIncreased incidence of cutaneous mycobacterial infection was detected from 2019 to 2021. The most common infecting pathogen was M. marinum followed by M. abscessus. The sensitivity, specificity and accuracy of the skin tissue culture method were 70%, 100% and 76.62%, respectively, while that of the DNA microarray chip assay were 91.67%, 100% and 93.51%, respectively. The sensitivity and accuracy of the DNA microarray chip assay were significantly higher than those of the skin tissue culture method. The positive likelihood and diagnostic odds ratio were >10 and >1, respectively for both the methods. The negative likelihood ratio was significantly higher (30% vs 8.33%) and the Youden’s index was significantly lower (70.00% vs 91.67%) in the skin culture method compared to that of the DNA microarray chip assay. There was a significant association of false negative results with a history of antibiotic use in the skin tissue culture method.DiscussionGiven the increasing incidence of cutaneous mycobacterial infections, early diagnosis remains a prime clinical focus. The DNA microarray chip assay provides a simple, rapid, high-throughput, and reliable method for the diagnosis of cutaneous mycobacterial infections with potential for clinical application.